The presence of leuko-araiosis in patients with Alzheimer's disease predicts poor tolerance to tacrine, but does not discriminate responders from non-responders. - Amar, K; Wilcock, G; Scot, M; Lewis, T (1997)
BACKGROUND: approximately one-third of patients with Alzheimer's disease (AD) respond favourably to the anticholinesterase tacrine, but the drug's usefulness is marred by a high incidence of side-effects. OBJECTIVE: to discover if AD patients with white matter low attenuation (WMLA) represents a subgroup that responds differently to tacrine from those with no WMLA. DESIGN: the results come from a combination of double-blind and open studies. Seventy-two AD patients prescribed tacrine in our centre were divided into two groups according to the presence or absence of WMLA on brain CT scans. We compared the rate of response to and withdrawal from tacrine between the groups. Response was defined as an improvement in the Mini-Mental State Examination score of three or more points at 3 months. RESULTS: 18 of the 72 patients were found to have WMLA. There was no significant difference in the proportion of patients responding to tacrine in each group (28.5% in those with WMLA and 31% in those without), but the rate of withdrawal from tacrine did differ: 11 patients with WMLA (61%) had to be withdrawn prematurely, compared with 14 patients (26%) in the group without evidence of WMLA (P = 0.015). CONCLUSION: AD patients with WMLA can still respond to tacrine, although the rate of withdrawal from treatment is much higher in such patients.